Social networks and digital influencers: their role In customer decision journey in tourism - Guerreiro, C (2020)
Several studies have shown the impact of social media on tourism and the role of digital influencers. However, the relationship between social media, digital influencers, and the customer decision journey has not been much studied. To help fill this gap, the present study examines the role of digital influencers during each phase of the customer decision journey using an online survey. The findings from 244 social media users show that the majority use social networks when planning a trip, however, sharing the experiences of other travellers is not a relevant aspect. While, overall, digital influencers have no significant impact, their followers tend to value their content, visit the sites they suggest, and share their own experiences, mostly through Instagram.